Stress and eating behaviors in children and adolescents: Systematic review and meta-analysis. (1st April 2018) - Hill, Deborah C.; Moss, Rachael H.; Sykes-Muskett, Bianca; Conner, Mark; O'Connor, Daryl B.
Abstract: It is well established that stress is linked to changes in eating behaviors. Research using adult populations has shown that stress is associated with both increases and decreases in the amount and type of food consumed. However, due to a lack of research reviews, the relationship between stress and eating behaviors in children is unclear. This systematic research review and meta-analysis aimed to identify whether stress is associated with healthy and unhealthy eating behaviors in children aged 8–18 years. Studies were included in the review if they measured stress and included a measure of food consumption. All unique studies retrieved ( N = 28, 070) were assessed for their eligibility at title, abstract and full text levels. A total of 13 studies were included in the final review and data were analysed using Comprehensive Meta-Analysis. Using random-effects modelling, overall stress was not associated with a change in overall eating behaviors. However, additional analyses indicated stress was associated with unhealthy eating behaviors in both younger ( Hedge's g = 0.283, p < 0.001) and older ( Hedge's g = 0.274, p = 0.001) children. In contrast, stress was not associated with healthy eating behaviors in younger children ( Hedge's g = 0.093, p = 0.156), but was negatively associated with healthy eating behaviors in older children ( Hedge's g = −0.384, p < 0.001). The current findings are concerning as they suggest the impact of stress on unhealthy eating may begin as early as 8 or 9 years old. Future research ought to investigate further the role of psychological, behavioral and endocrine factors in the development of stress-related eating in children.